2017
DOI: 10.1080/21622965.2017.1378579
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of expressive vocabulary in school-age children: Development and application of the Kilifi Naming Test (KNT)

Abstract: The dearth of locally developed measures of language makes it difficult to detect language and communication problems among school-age children in sub-Saharan African settings. We sought to describe variability in vocabulary acquisition as an important element of global cognitive functioning. Our primary aims were to establish the psychometric properties of an expressive vocabulary measure, examine sources of variability, and investigate the measure's associations with non-verbal reasoning and educational achi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 88 publications
1
7
0
Order By: Relevance
“… 12 A seven‐item battery was used to test verbal and non‐verbal skills in the 2001 survey. 12 In 2015, the Raven’s Coloured Progressive Matrices 22 and Kilifi Naming Test 23 were administered to evaluate non‐verbal skills and language/communication deficits respectively. We defined cognitive impairments using z‐scores from these neuropsychological scores standardized to the general population.…”
Section: Methodsmentioning
confidence: 99%
“… 12 A seven‐item battery was used to test verbal and non‐verbal skills in the 2001 survey. 12 In 2015, the Raven’s Coloured Progressive Matrices 22 and Kilifi Naming Test 23 were administered to evaluate non‐verbal skills and language/communication deficits respectively. We defined cognitive impairments using z‐scores from these neuropsychological scores standardized to the general population.…”
Section: Methodsmentioning
confidence: 99%
“…Our results support those of Pretorius and Stoffelsma (2017) who found that children older than expected in Grade 3 performed more poorly on vocabulary. Our focus on children who should have been in the Grade 3 cohort reduced the variation in vocabulary due to age, explaining why our findings differ from those of Kitsao-Wekulo et al (2019), for example Knauer et al (2019) and Mazibuko and Chimbari (2020).…”
Section: Discussionmentioning
confidence: 59%
“…Recent studies have started to address these concerns by developing tests in African languages. Kitsao-Wekulo et al (2019) created the Kilifi Naming Test (KNT), which allows multilingual participants to name lexical items in any of their languages (English, Swahili, and a local language). The KNT was validated on primary school children, and it was found that age, number of years in school, and living in a rural area was positively associated with multilingual productive vocabulary.…”
Section: Vocabulary Research In Sub-saharan Africamentioning
confidence: 99%
“…The Kilifi Naming Test was developed in Kenya to measure expressive vocabulary among children in a rural setting ( Kitsao-Wekulo et al, 2019 ). The child must provide labels for a selection of pictures presented in black and white with or without cues.…”
Section: Methodsmentioning
confidence: 99%